Pengaruh Logo Halal, Word of Mouth, dan Kualitas Produk terhadap Keputusan Pembelian Mie Kober (Studi pada Konsumen Mie Kober cabang Soekarno Hatta) - Maharisna, Robby Yudha; Rizal, Mohammad; Rahman, Fahrurrozi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The aim of this research is to see the impact of the Halal Logo, Word of Mouth, and Product Quality on Purchasing Decisions for Mie Kober at the Soekarno Hatta branch. The population in this research are consumers who have made purchases at Mie Kober Soekarno Hatta branch with a sample size of 64 people, using the purposive sampling method. The data collection technique used in this research was carried out by distributing questionnaires via Google Form. Research data was analyzed using IBM SPSS software. The research results show that simultaneously the Halal Logo, Word of Mouth, and Halal Logo have a significant effect on Purchasing Decisions. The Halal Logo has a significant influence on Purchasing Decisions. Word of Mouth does not have a significant effect on Purchasing Decisions. Product quality has a significant effect on purchasing decisions Keywords: Halal Logo, Word of Mouth, Product Quality, Purchase Decision, Mie Kober